Do‐it‐Yourself Mock Community Standard for Multi‐Step Assessment of Microbiome Protocols. Issue 9 (6th September 2022) - Colovas, Joanna; Bintarti, Ari Fina; Mechan Llontop, Marco E.; Grady, Keara L.; Shade, Ashley
Abstract: Microbiomes provide critical functions that support animals, plants, and ecosystems. High‐throughput sequencing (HTS) has become an essential tool for the cultivation‐independent study of microbiomes found in diverse environments, but requires effective and meaningful controls. One such critical control is a mock microbial community, which is used as a positive control for nucleic acid extraction, marker gene amplification, and sequencing. While mock community standards can be purchased, they can be costly and often include only medically relevant microbial strains that are not expected to be major players in non‐human microbiomes. As an alternative, it is possible to design and construct a do‐it‐yourself (DIY) mock community, which can then be used as a positive control that is specifically customized to the protocol needs of a particular study system. In this article, we describe protocols to select appropriate microbial strains for the construction of a mock community. We first describe the steps to verify the identity of community members via Sanger sequencing. Then, we provide guidance on assembling and storing the DIY mock community as viable whole cells. This includes steps to create standard growth curves referenced to plate counts for each member, so that the community members can be quantified and later compared in terms of their "expected versus returned" relative contributions after sequencing. We also describe appropriate methods for the cryostorage of the fully assembled mock community as viable whole cells, so that they can be used as a unit in a microbiome analysis, from the lysis and nucleic acid extraction steps onwards. Finally, we provide an example of returned data and interpretation of DIY mock community sequences, discussing how to assess possible contamination and identify protocol biases for particular members. Overall, DIY mock communities serve to determine success and possible bias in a cultivation‐independent microbiome analysis. © 2022 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Strain identification and verification using Sanger sequencing Basic Protocol 2 : Creation of glycerol stocks of each mock community strain for long‐term cryostorage Basic Protocol 3 : Assessment of strain freezer viability without cryoprotectant Basic Protocol 4 : Creation of standard curve to determine CFU/ml of a liquid culture as a function of optical density Basic Protocol 5 : Full mock community assembly using community concentration calculations and standard curves